Five Years of First Year Math: An Analysis of Student Success Outcomes Following the Implementation of EO 1110, Academic Years 2018-19 to 2022-23 - Kristin M. Jordan:::::: (2023)
In Fall 2018, CSU Channel Islands (CSUCI) began implementing CSU Executive Order (EO) 1110. EO 1110 calls for the enrollment of new freshmen in college credit-bearing courses to satisfy B4 (Mathematics/Quantitative Reasoning) and A2 (Written Communication) General Education (GE) courserequirements. EO 1110 also dictates how those students are placed in the recommended courses. Within the CSU system, students are assigned one of four math/quantitative reasoning placement statuses: M1 (fulfilled GE B4 requirements), M2 (placement in GE B4 course), M3 (GE B4 course with support recommended), M4 (GE B4 course with support or stretch required).1 assumption/inclination is to think that the support course (with better continuity) is a better option than the year-long stretch.